2022
DOI: 10.7306/gq.1639
|View full text |Cite
|
Sign up to set email alerts
|

Rietveld crystal structure refinement of a natural rhombohedral grossular-andradite garnet from Serbia

Abstract: As so ci ate Editor: Tomasz Bajda Four mac ro scop i cally vis i ble B-E (rim) zones, within a large nat u ral fer ric grossular gar net of Grs 58-64 Adr 36-42 Sps 2 com po sition, are de scribed by means of Rietveld re fine ments of the crys tal struc tures in a se ries of six space groups, fol lowed by com par a tive anal y sis of the R-val ues, site oc cu pancy fac tors, and bond lengths and an gles. The gar net crys tal lized in the rhombohedral R63c space group. Var i ous poly he dral dis tor tions and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…To examine these data and mutual correlations between the UCPs, we used MS Excel to calculate statistical parameters and the coefficients of the regression-R 2 (hereinafter correlations-C). These correlations, reported in our previous studies of different materials (Cvetković and Tančić, 2019; Tančić et al , 2021; Maksimović et al , 2023) are proven useful accessory tools, which allow the comparison between various parameters. According to the results, a polynomial regression between the a 0 , c 0 and V 0 parameters gives slightly better R 2 coefficients than linear regression (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…To examine these data and mutual correlations between the UCPs, we used MS Excel to calculate statistical parameters and the coefficients of the regression-R 2 (hereinafter correlations-C). These correlations, reported in our previous studies of different materials (Cvetković and Tančić, 2019; Tančić et al , 2021; Maksimović et al , 2023) are proven useful accessory tools, which allow the comparison between various parameters. According to the results, a polynomial regression between the a 0 , c 0 and V 0 parameters gives slightly better R 2 coefficients than linear regression (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 63%
“…(v) The option that various structural variations within the samples could take place Although the crystal structure refinements are beyond the scope of this paper, our previous studies of diverse mineral species and solid solutions, have demonstrated that the different UCPs, polyhedral distortions, site occupancy factors, bond lengths, bond angles and valence units, could be influenced either by: (1) different inserted cations into the mineral structure; and/or by ( 2) diverse conditions of their formation, in particular, the temperature and pressure (Tančić 2017(Tančić , 2018Tančić and Kremenović, 2022;Tančić et al, 2012Tančić et al, , 2020Tančić et al, , 2023.…”
Section: (Iii) Presence Of Other Phasesmentioning
confidence: 99%
“…We believe that the weak garnet anisotropy could indicate the presence of disymmetrization; there are five possible causes of this, discussed in [4][5][6]. In summary, it is agreed that the that grossular-andradite garnet group could exhibit non-cubic symmetry in various space groups (hereinafter, s.g.'s), such as: I‾1 [9][10][11][12][13][14]; Fddd [9,12,15,16]; Fddd or C2/c [17]; R‾3c or Fddd [5]; and R‾3c [6]. More recently, it was shown that these minerals could have a tetragonal symmetry (most likely I41/a s.g.), as well [18].…”
Section: Introductionmentioning
confidence: 99%
“…Only three optically anisotropic grossular-andradite garnets from Serbia have been characterized so far (i.e., from skarns found in the Kopaonik Mts. [4][5][6], Rogozna Mts. [7], and Rudnik Mts.…”
Section: Introductionmentioning
confidence: 99%
“…At last, a single remaining solution should be taken into consideration. (v) Although the crystal structure re nements are beyond the scope of this paper, our previous studies of various mineral species, and solid-solutions, have demonstrated that the different unit-cell parameters, various polyhedral distortions, site occupancy factors, bond lengths, bond angles, valence units, etc., could be induced either by (a) the different inserted cations into the mineral structure; or/and by (b) the different conditions of their formation, in particular, the temperature and pressure(Tančić 2017(Tančić , 2018Tančić and Kremenović 2022;Tančić et al 2012Tančić et al , 2020.…”
mentioning
confidence: 99%